Single-molecule study of DNA structure and dynamics by Forster Resonance Energy Transfer (FRET) - Ricksen Surya Winardhi. (2009)
G-quadruplex DNA is formed by tetrads of guanines. It has an immense biological importance, yet it has extreme conformational diversity. Ensemble methods is not capable of observing these structural dynamics. Single-molecule techniques has come to rescue due to its capability to probe individual molecule and its time trajectories. In this project, single-molecule Forster resonance energy transfer system is constructed, and this state of the art system will be used for studying single G-quadruplex DNA dynamics. The result reveals the time trajectories of single G-quadruplex conformational changes, as well as the proposed conformations associated with it.